Design and Optimization of a Layered Polymer Injection Flow Control Valve for Enhanced Oil Recovery via Polymer Flooding - Ma, Haifeng; Chen, Taiyu; Yan, Xinxin (Scientific Journal of Technology, 2026)
Focusing on the issue of severe viscosity loss in the flow control valve, a core component of polymer flooding for enhanced oil recovery, this study takes the layered polymer injection flow control valve as the research object. A numerical simulation and structural optimization based on low shear rate conditions were conducted, and experiments were performed to verify the feasibility of the optimized design. Using the control variable method, numerical simulations were carried out on different valve spool structures, slot spacing, slot depth, and valve stem length. The results demonstrate that the circular arc spool flow control valve exhibits superior viscosity preservation performance compared to other shapes. When the slot spacing is 30 mm, slot depth is 3 mm, and valve stem length is 1 mm, the viscosity preservation performance is optimal. Orthogonal experiments reveal that slot depth has the most significant impact on shear rate and validate the accuracy of single-factor analysis. Field experiments measured a maximum viscosity loss rate of 8.9%, which is a significant improvement compared to the 12% loss observed in other oilfields, confirming the enhanced viscosity preservation effect of the optimized flow control valve. This study provides theoretical support for the optimization of layered polymer injection tools.